(untitled) (Journal of Ideas in Health, 2021)
Background: Even though Real-Time Polymerase Chain Reaction (RT-PCR) is a gold standard for confirming COVID-19, it continues to be plagued by a lack of RT-PCR kits and the potential of false-negative results. Hence, during the second wave of COVID-19 in India, Computed Tomography (CT) scan is an emerging diagnostic tool in evaluating the severity of illness in COVID-19 pneumonia. The present study endeavored to assess chest CT features of COVID-19 pneumonia in Indian population. Methods: This was a single-center, retrospective, observational study conducted in 300 consecutive adults RT-PCR confirmed COVID-19 patients from 1, Jan 2021 to 31, March 2021 at a private radio diagnostic center. Data regarding baseline demographics, clinical and laboratory characteristics, extent, pattern, and type of abnormal CT findings were noted. Results: The study population (204 males and 108 females) had mean age of 43.18 ± 8.27 years. Our study’s most common clinical presentation was cough (48.1%) and fever (47.1%), respectively. Lung parenchymal abnormalities were found in 294 (94.2%) patients. Abnormal CT findings revealed the involvement of bilateral (45.6%) and multilobar (42.9%) with a predominant peripheral (92.3%) and posterior (80.8%) distribution. According to the type of opacity, Ground Glass Opacity (GGO) was the dominant abnormality found in 270 (91.8%) patients, in which pure GGO (36.7%), GGO with crazy paving pattern (39.8%), and GGO mixed with consolidation (52.0 %) were noted. Peri-lesional or intralesional segmental or subsegmental pulmonary vessel enlargement was found in 192 (65.3 %) patients. Conclusion: During the second wave of COVID-19, a chest CT scan is a modality of choice in diagnosing COVID-19 pneumonia and related lung parenchymal changes.